HAMBATAN TEKNOLOGI YANG DIHADAPI PELAKU UMKM DALAM PEMANFAATAN PLATFROM GRABFOOD : KEDAI MBAK WIWIK - Elvina Zailanty Harahap; Ocha Pratika, Zainarti (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
The use of digital platforms such as GrabFood provides a great opportunity for MSMEs to expand their market and increase sales. However, many MSMEs still face obstacles, especially in terms of technology and digital systems. This study uses a qualitative descriptive approach with semi-structured interviews with MSMEs, one of which is Kedai Mbak Wiwik. The main obstacles include low digital literacy, limited access to technology, high commission fees, administrative complexity, and lack of assistance. The case study shows that the most dominant difficulty experienced by Kedai Mbak Wiwik is in understanding and withdrawing funds from the application to a personal account, due to a lack of understanding of the digital financial system. To overcome these obstacles, the proposed strategic solutions include digital literacy training, provision of shared technology facilities, simplified procedures, subsidy commissions, and assistance for community-based programs. This solution is expected to empower MSMEs to be better prepared to face digital transformation.